RESEARCH OF CONSUMPTION PROPERTIES OF ORGANIC SYRUPS - TKACHENKO, Alina (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The paper presents the results of research on organoleptic parameters, glycemic index, nutritional value and safety indicators of organic syrups. Organoleptic characteristics of syrups (taste, aroma, color and appearance) were studied by sensory analysis. Determination of glycemic index and nutritional value was carried out on the basis of analytical data by comparison. To study the content of toxic elements in the products used conventional methods: lead and cadmium were determined by the atomic absorption method, mercury - by the method of flameless atomic absorption. The objects of the study are: organic maple syrup "Maribel" 330 g (250 ml), country of production - Canada; organic agave syrup "Bio syrop z agawy" (650 g) - country of manufacture Mexico; Horizon organic rice syrup (450 g) is a country of production in the Netherlands. It was found that all the studied syrups have a pleasant taste and aroma, and the addition of organic syrups to the recipes of flour products can improve their organoleptic properties, giving an exotic flavor. Rice syrup has the highest glycemic index among the studied syrups (98). The lowest glycemic index is characterized by agave syrup (17), but such a low glycemic index is characteristic only of agave syrups of Mexican origin. The energy value of sugar and rice syrup is the same and is 396 kcal. At the same time, the lowest caloric content is a sample of maple syrup - 262 kcal. The same syrup contains the lowest amount of carbohydrates - 67.5 g / 100 g. Agave syrup contains slightly more carbohydrates - 76.37 g / 100 g. The fat content in syrups is very limited and contains 0.20 g / 100 g in maple and rice syrups, and agave syrup - 0.45 g / 100 g. The protein content of maple syrup is absent, and agave syrup and rice syrup are almost invisible - 0.09 g / 100 g and 0.60 g / 100 g, respectively. In terms of the content of heavy metal salts in syrups, the products can be considered safe. The lead content is the lowest in maple syrup (0.03 mg / kg), and the cadmium and mercury content is the same in all test samples and is 0.01 mg / kg and 0.001 mg / kg for each sample, respectively. Further research is planned to create recipes based on organic syrups and analysis of nutritional and biological value based on them.